Household Risk Management and Social Protection in Chile. (World Bank country study., 2005)
"This report examines whether Chile has a social protection "system"--Broadly defined to include policy interventions, public institutions, and the regulation of private institutions that lower the welfare costs of adverse shocks to income from job loss and extended unemployment, health episodes, old age, and life-time poverty - or instead has a set of loosely-coordinated programs. It assesses whether households are provided with appropriate tools to mitigate risks to their income, and identifies gaps in coverage and where instruments are missing. Finally, the study provides the Government with a set of guidelines, grounded in a conceptual framework, that, if carefully applied, could increase the effectiveness of social protection."--Jacket